Estimating the effect of sulfonylurea on HbA1c in diabetes: a systematic review and meta-analysis - Hirst, J; Farmer, A; Dyar, A; Lung, T; Stevens, R (Springer-Verlag, 2013)
AIMS/HYPOTHESIS: Sulfonylureas are widely prescribed glucose-lowering medications for diabetes, but the extent to which they improve glycaemia is poorly documented. This systematic review evaluates how sulfonylurea treatment affects glycaemic control. METHODS: Medline, EMBASE, the Cochrane Library and clinical trials registries were searched to identify double-blinded randomised controlled trials of fixed-dose sulfonylurea monotherapy or sulfonylurea added on to other glucose-lowering treatments. The primary outcome assessed was change in HbA1c, and secondary outcomes were adverse events, insulin dose and change in body weight. RESULTS: Thirty-one trials with a median duration of 16 weeks were included in the meta-analysis. Sulfonylurea monotherapy (nine trials) lowered HbA1c by 1.51% (17 mmol/mol) more than placebo (95% CI, 1.25, 1.78). Sulfonylureas added to oral diabetes treatment (four trials) lowered HbA1c by 1.62% (18 mmol/mol; 95% CI 1.0, 2.24) compared with the other treatment, and sulfonylurea added to insulin (17 trials) lowered HbA1c by 0.46% (6 mmol/mol; 95% CI 0.24, 0.69) and lowered insulin dose. Higher sulfonylurea doses did not reduce HbA1c more than lower doses. Sulfonylurea treatment resulted in more hypoglycaemic events (RR 2.41, 95% CI 1.41, 4.10) but did not significantly affect the number of other adverse events. Trial length, sulfonylurea type and duration of diabetes contributed to heterogeneity. CONCLUSIONS/INTERPRETATION: Sulfonylurea monotherapy lowered HbA1c level more than previously reported, and we found no evidence that increasing sulfonylurea doses resulted in lower HbA1c. HbA1c is a surrogate endpoint, and we were unable to examine long-term endpoints in these predominately short-term trials, but sulfonylureas appear to be associated with an increased risk of hypoglycaemic events.